Potential negative consequences of geoengineering on crop production: A study of Indian groundnut - Yang, Huiyi; Dobbie, Steven; Ramírez Villegas, Julián Armando; Feng, Kuishuang; Challinor, Andrew J.; Chen, Bing; Gao, Yao; Lee, Lindsay; Yin, Yan; Sun, Laixiang; Watson, James; Köhler, Ann-Kristin; et al. (Wiley, 2016)
Geoengineering has been proposed to stabilize global temperature, but its impacts on crop production and stability are not fully understood. A few case studies suggest that certain crops are likely to benefit from solar dimming geoengineering, yet we show that geoengineering is projected to have detrimental effects for groundnut. Using an ensemble of crop-climate model simulations, we illustrate that groundnut yields in India undergo a statistically significant decrease of up to 20% as a result of solar dimming geoengineering relative to RCP4.5. It is somewhat reassuring, however, to find that after a sustained period of 50 years of geoengineering crop yields return to the nongeoengineered values within a few years once the intervention is ceased.